A TPE–benzothiazole piezochromic and acidichromic molecular switch with high solid state luminescent efficiency. Issue 12 (7th February 2018) - Ma, Chunping; He, Jiajun; Xu, Bingjia; Xie, Gaoyi; Xie, Zongliang; Mao, Zhu; Chi, Zhenguo
Abstract : A new organic compound, namelyB-TPEAN, was constructed by using tetraphenylethylene, acrylonitrile and benzothiazole as building blocks. Abstract : A new organic compound, namelyB-TPEAN, was constructed by using tetraphenylethylene, acrylonitrile and benzothiazole as building blocks. Herein, results of single crystal structure analysis and theoretical calculation for the as-synthesized compound were presented. Photophysical properties, including UV-visible absorption, photoluminescence and fluorescent quantum yield, were also well studied.B-TPEAN was found to show excellent aggregation-induced emission (AIE) properties and high quantum yield (up to 85%) in the solid-state. These results should be attributed to the positive effect of a combination of two typical AIE moieties in one molecule. Upon grinding, the emission color of the pristine sample forB-TPEAN changed from bluish green ( λ em, max = 497 nm) to yellow ( λ em, max = 567 nm), exhibiting a remarkable piezochromism. Moreover, by fuming with acid vapor, both of the pristine and the ground samples ofB-TPEAN showed dramatic decreases in fluorescence quantum yields and large bathochromic shifts in PL maxima up to 53 nm and 80 nm, respectively, indicating a success in achieving multi-stimuli-responsive luminophore with high contrast in both emission intensity and color. Further investigation revealed that the acidifluorochormism of the samples was caused by the protonation of the benzothiazole moiety, leading to an enhancement of ICT effect in the protonated molecules.